Activation of Glucocorticoid Receptor Inhibits the Stem-Like Properties of Bladder Cancer via Inactivating the β-Catenin Pathway - Xu, Congcong; Sun, Mingwei; Zhang, Xiaozhen; Xu, Zhen; Miyamoto, Hiroshi; Zheng, Yichun (Frontiers in Oncology, 2020)
Background: Glucocorticoid receptor (GR) signaling pathway was shown in vitro to affect epithelial -to- mesenchymal transition which was implicated in the regulation of bladder cancer stem cells (CSCs) in our previous study. Herein, we want to figure out how the stem-like properties of bladder cancer behave when activate or inhibit GR pathway. Methods: In order to study whether GR can modulate bladder CSCs, we used dexamethasone (DEX) to activate GR pathway or gene-knockdown (KD)/-knockout (KO) techniques to silence GR pathway. Then we applied immunohistochemical staining and flow cytometry to study whether the level of GR expression would influence CD44, stem cell surface marker expression. The association between GR signal pathway and stem-like properties was investigated by reactive oxygen species (ROS), sphere-formation and side population assays using GR-positive/-knockdown/-knockout cell lines. The expression level of cancer stem cell associated-genes, including Beta-catenin, C-MYC, Snail and OCT-4 was assessed by PCR and Western Blotting. Bladder cancer GR-positive/-knockdown/-knockout cells’ oncogenicity was quantified by mouse xenograft. Results: We found that activation of GR pathway could significantly decrease the expression of CD44, reduce the rate of sphere formation, lessen the proportion of side populations, decrease the expression of pluripotency-related transcription factors (Beta-catenin, C-MYC, OCT-4, Snail) and increase the intracellular levels of ROS, but GR-KD/-KO groups have the opposite effect. In xenograft-bearing mice, GR gene-knockout contributed to the enhancement of bladder cancer tumorigenicity. Conclusions: These data revealed that the activation of GR pathway inhibited stem-like properties, and it might be done via downregulating beta-catenin pathway.